A graphene–melamine-sponge for efficient and recyclable dye adsorption. Issue 59 (7th June 2016) - Du, Qingchuan; Zhou, Ying; Pan, Xuwei; Zhang, Jiaoxia; Zhuo, Qiqi; Chen, Shangtao; Chen, Guangming; Liu, Tengfei; Xu, Fan; Yan, Chao
Abstract : The submersible graphene–melamine-sponges present fast and highly efficient adsorption for water soluble dyes. Abstract : Graphene sponges have attracted extensive interest as adsorbents. However, the hydrophobic nature of graphene hinders the submergence of graphene sponge into the water solution. In the present study, we developed a graphene–melamine-sponge (GMS) that can readily submerge into water solution with the help of a superhydrophilic melamine skeleton and investigated its adsorption behaviors for methylene blue (MB) and orange G (OG). The obtained GMS efficiently adsorbed methylene blue with competitive capacity. Isotherm analysis indicated that the adsorption corresponded to the Langmuir isotherm model in a monolayer manner. The maximum adsorption capacities for MB and OG obtained from the Langmuir isotherm equation are 286.5 mg g −1 and 80.51 mg g −1, respectively. Kinetic studies showed that the adsorption followed a pseudo-second-order kinetics model. The as-prepared GMS could be easily regenerated and maintained 95% adsorption capacity after 10 cycles.